The mystic Jesus : the mind of love - Williamson, Marianne, 1952- (The Marianne Williamson series, 2024)
"Returning to the topic of her beloved classic bestseller Return to Love, spiritual guide Marianne Williamson builds on the ideas introduced in that book to lead us toward the light through the inspiring guidance of the mystic Jesus"--